2014
DOI: 10.1016/j.semradonc.2014.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Image Guided Brachytherapy

Abstract: The application of MRI-guided brachytherapy has demonstrated significant growth during the last two decades. Clinical improvements in cervix cancer outcomes have been linked to the application of repeated MRI for identification of residual tumor volumes during radiotherapy. This has changed clinical practice in the direction of individualized dose administration, and mounting evidence of improved clinical outcome with regard to local control, overall survival as well as morbidity. MRI-guided prostate HDR and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 78 publications
0
86
0
Order By: Relevance
“…Associations with outcome were demonstrated for two cohorts recruited over a time period of 11 years, during which MR image-guided brachytherapy has been implemented in our hospital and replaced brachytherapy based on 2D X-ray imaging (36). Moreover, the second cohort was analyzed with another Illumina array generation, which required data transformation prior to classification.…”
Section: Discussionmentioning
confidence: 99%
“…Associations with outcome were demonstrated for two cohorts recruited over a time period of 11 years, during which MR image-guided brachytherapy has been implemented in our hospital and replaced brachytherapy based on 2D X-ray imaging (36). Moreover, the second cohort was analyzed with another Illumina array generation, which required data transformation prior to classification.…”
Section: Discussionmentioning
confidence: 99%
“…7 Magnetic resonance imaging (MRI) is increasingly used for treatment planning due to the improved visualization of tumors and the surrounding critical organs. 8 International standards for contouring locally advanced cervical cancer rely on MRI.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the position and orientation of the needle at 2 are (0, 5, 8) and (-2, -0.5, -4), respectively. The calculated paths for ball joints revealed that 1 traveled between the points (-5, 5, 0) and (4,6,0). Similarly, 2 moved between the points (-4, 4, 4) and (2, 5.5, 4).…”
Section: Resultsmentioning
confidence: 99%